Efektivitas Penggunaan Aplikasi Sistem Pengelolaan Pengaduan Pelayanan Publik Nasional – Layanan Aspirasi Pengaduan Online Rakyat (SP4N-LAPOR!) - Elin Ayu Sariti; Usep Dayat; Gun Gun Gumilar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The government continues to innovate in providing satisfactory public services. One of these innovations is SP4N-LAPOR!, a technology-based public complaint management system. Bekasi city is one of the regions that has implemented SP4N-LAPOR!, managed by the Communication, Informatics, Statistics, and Encryption Office (Diskominfostandi). This research aims to determine the effectiveness of the SP4N-LAPOR! application in Bekasi City using Budiani (2007) as cited in (Purnamawati et al., 2022) effectiveness theory, which includes four indicators: program targeting, program socialization, program objectives, and program monitoring. This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that the effectiveness of SP4N-LAPOR! in Bekasi City is not yet fully optimal. This is due to lack of socialization by the local government, limited human resources. The conclusion of this study is that the use of SP4N-LAPOR! in Bekasi City is quite effective, but it still requires improvements in terms of socialization, evaluation, and technical support.